Associations of observed home dampness and mold with the fungal and bacterial dust microbiomes. Issue 3 (1st March 2021) - Cox, Jennie; Stone, Timothy; Ryan, Patrick; Burkle, Jeff; Jandarov, Roman; Mendell, Mark J.; Adams, Rachel I.; Niemeier-Walsh, Christine; Reponen, Tiina
Abstract : This study is an exploration of the indoor microbiome and its association with visible mold and moisture damage. Specific species of fungus and bacteria increase or decrease with increasing mold or moisture damage. Abstract : The objective of this analysis was to examine and compare quantitative metrics of observed dampness and mold, including visible mold and moisture damage, and fungal and bacterial microbiomes. In-home visits were conducted at age 7 for children enrolled in the Cincinnati Childhood Allergy and Air Pollution Study. Trained study staff evaluated the primary residence and measured total areas of visible moisture and mold damage in the home. Floor dust was collected and archived. Archived dust samples collected from each home ( n = 178) were extracted and analyzed using bacterial (16S rRNA gene) and fungal (internal transcribed spacer region) sequencing. Fungi were also divided into moisture requirement categories of xerophiles, mesophiles, and hydrophiles. Data analyses used Spearman's correlation, Kruskal–Wallis, Permanova, DESeq, and negative binomial regression models. Comparing high moisture or mold damage to no damage, five fungal species and two bacterial species had higher concentrations (absolute abundance) and six fungal species and three bacterial species had lower concentrations. Hydrophilic and mesophilic fungi showed significant dose-related increases with increasing moisture damage and mold damage, respectively. When comparing alpha or beta diversity of fungi and bacteria across mold and moisture damage levels, no significant associations or differences were found. Mold and moisture damage did not affect diversity of fungal and bacterial microbiomes. Instead, both kinds of damage were associated with changes in species composition of both bacterial and fungal microbiomes, indicating that fungal and bacterial communities in the home might be influenced by one another as well as by mold or moisture in the home.